PENGARUH KUALITAS PRODUK DAN DISTRIBUSI TERHADAP LOYALITAS PELANGGAN PEMESANAN LAMPU PADA PT SOLARENS LEDINDO - Iin Surtiah; Gunardi Gunardi; Hendriady de Keizer; Idah Rosidah (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2022)
The purpose of this study was to test and analyze the effect of Product Quality, Distribution on Customer Loyalty. The decrease in Customer Loyalty is due to the inadequate Product Quality, Distribution Channels. The theory used is related to product quality, distribution channels and customer satisfaction and customer loyalty. The population in this study amounted to 216 customers and a sample of 140 customers. The sampling technique used was random sampling. The data analysis used was validity and reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing. The conclusion in this study is that partially and simultaneously Product Quality, Distribution Channels and Customer Satisfaction have a positive and significant effect on Customer Loyaltyat PT Solarens Ledindo.